AB1082 INFLUENCE OF THE VARIATION OF THE OPERATOR, PATIENT POSITION AND DEVICE ON THE MEASUREMENT PERFORMANCE OF RADIOFREQUENCY ECHOGRAPHIC MULTI SPECTROMETRY (REMS). (2nd June 2020) - Caffarelli, C.; Adami, G.; Arioli, G.; Bianchi, G.; Brandi, M. L.; Casciaro, S.; Cianferotti, L.; Ciardo, D.; Conversano, F.; Gatti, D.; Girasole, G.; Manfedini, M.; et al.
Abstract : Background: The monitoring of bone mineral density (BMD) is a key aspect for patients undergoing pharmacological treatments that might cause BMD changes at non-physiological rates. At present, the short-term follow-up of patients under treatment in terms of BMD change with time remains an unmet clinical need, since the current techniques, including the gold standard dual X-ray absorptiometry (DXA), require at least 1 year between two consecutive measurements [1]. Therefore, an effective strategy for the assessment of BMD should guarantee high accuracy, precision and repeatability of the measurements. Objectives: The aim is to assess the influence of the variation 1) in patient position, 2) operator (both intra- and inter-) and 3) device on the REMS performance at lumbar spine and femoral neck. Methods: 210 women were enrolled, divided in 7 groups of 30-patient each for the assessment of the parameters of interest, i.e. inter-device, intra- and inter-operator repeatability for lumbar spine scans and inter-patient position, inter-device, intra- and inter-operator repeatability for femoral neck scans. All patients underwent 2 REMS scans at lumbar spine or femoral neck, performed by the same operator or by 2 different operators or by the same operator using 2 different devices or in different patient position (i.e. supine without constraints or with a constrained 25°-rotation of the leg). The percentage coefficient of variation (CV%) with 95% confidence interval and least significant change for a 95% confidence level (LSC) have been calculated. Results: For lumbar spine, intra-operator repeatability resulted in CV%=0.37% (95%CI: 0.26%-0.48%), with LSC=1.02%, inter-operator repeatability resulted in CV%=0.55% (95% CI: 0.42%-0.68%), with LSC=1.52%, inter-device repeatability resulted in CV%=0.53% (95% CI: 0.40%-0.66%), with LSC=1.47%. For femoral neck, intra-operator repeatability resulted in CV%=0.33% (95%CI: 0.23%-0.43%), with LSC=0.91%, inter-operator repeatability resulted in CV%=0.47% (95% CI: 0.35%-0.59%), with LSC=1.30%, inter-device repeatability resulted in CV%=0.42% (95% CI: 0.30%-0.51%), with LSC=1.16%, inter-patient position repeatability resulted in CV%=0.24% (95% CI: 0.18%-0.30%), with LSC=0.66%. Conclusion: REMS densitometry is highly precise for both anatomical sites, showing high performance in repeatability. These results suggest that REMS might be a suitable technology for short-term monitoring. Moreover, thanks to its ionizing radiation-free approach, it might be applied for population mass investigations and prevention programs also in paediatric patients and pregnant women. References: Note : Carla Caffarelli, Giovanni Adami §, Giovanni Arioli §, Gerolamo Bianchi §, Maria Luisa Brandi §, Sergio Casciaro §, Luisella Cianferotti §, Delia Ciardo §, Francesco Conversano §, Davide Gatti §, Giuseppe Girasole §, Monica Manfredini §, Maurizio Muratore §, Paola Pisani §, Eugenio Quarta §, Laura Quarta §, Stefano Gonnelli § Equal contributors listed in alphabetical order Disclosure of Interests: Carla Caffarelli: None declared, Giovanni Adami: None declared, Giovanni Arioli *: None declared, Gerolamo Bianchi Grant/research support from: Celgene, Consultant of: Amgen, Janssen, Merck Sharp & Dohme, Novartis, UCB, Speakers bureau: Abbvie, Abiogen, Alfa-Sigma, Amgen, BMS, Celgene, Chiesi, Eli Lilly, GSK, Janssen, Medac, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Sanofi Genzyme, Servier, UCB, Maria Luisa Brandi: None declared, Sergio Casciaro: None declared, Luisella Cianferotti: None declared, Delia Ciardo: None declared, Francesco Conversano: None declared, Davide Gatti Speakers bureau: Davide Gatti reports personal fees from Abiogen, Amgen, Janssen-Cilag, Mundipharma, outside the submitted work., Giuseppe Girasole: None declared, Monica Manfedini: None declared, Maurizio Muratore: None declared, Paola Pisani: None declared, Eugenio Quarta: None declared, Laura Quarta: None declared, Stefano Gonnelli: None declared